2020
DOI: 10.1177/0194599820970964
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Participation in Otolaryngology Telemedicine Clinic During COVID‐19: A Hidden Opportunity

Abstract: The undergraduate medical student educational experience was greatly altered this year due to coronavirus disease 2019. Many otolaryngology departments increased use of telemedicine technologies to avoid the need for in-person contact. Medical student incorporation into telemedicine clinics is important to increase their comfort with this format of patient care and to continue student exposure to the field of otolaryngology. The technical and logistical aspects of student inclusion in telemedicine clinics at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
“… Author Key findings Clinical competencies Site Specialty Country Dawoud et al [ 8 ] Students guided through curated surgical video content of select neurosurgical procedures by faculty. Students joined telemedicine clinics observing and participating after prior completion of online telehealth training modules 2,3,4,9,11,12 Univ Surgery US Pellegrini et al [ 9 ] 1-on-1 attending and 4th yr. med student telemedicine clinic from available exam room. Two computers to access electronic health records.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…51,[57][58][59] Finally, virtual telementoring initiatives have fostered continuity in resident and medical student training. [60][61][62][63]…”
Section: Covid-era Telemedicinementioning
confidence: 99%